Hanok: Architectural and Cultural Aspects of the Korean Traditional House - Donoso , Maria Daniela (Seven Editora, 2024)
This article seeks to approach Korean culture through the description and critical analysis of the house in hanok architecture, in addition to highlighting its technical-constructive and cultural aspects. Hanok is the term used to refer to buildings in the traditional Korean style. These had their main features crucially developed during the Joseon Dynasty (1392 -1897). Then, a critical analysis of the residential design typologies that make up this culture is developed. From these reflections, the repercussions of these architectural traditions and their contributions to the present day of this culture are also analyzed. DOI:https://doi.org/10.56238/sevened2024.018-077